Basis and Design of a Randomized Clinical Trial to Evaluate the Effect of Jinlida Granules on Metabolic Syndrome in Patients With Abnormal Glucose Metabolism - Jin, De; Hou, Lili; Han, Shuolong; Chang, Liping; Gao, Huailin; Zhao, Yiru; Zhao, Shenghui; An, Xuedong; Song, Guangyao; Piao, Chunli; Lian, Fengmei; Xiao-lin, Tong; et al. (Frontiers in Endocrinology, 2020)
Background: Metabolic syndrome (MS) is a powerful risk factor for cardiovascular and cerebrovascular diseases. Although lifestyle intervention reduces several of the symptoms of the syndrome and cardiovascular risks, the lifestyle intervention that yields the benefits is restrictive. Jinlida is a Chinese patent medicine that has shown activity in type 2 diabetes, which has been approved in China. Preclinical studies in Jinlida granules support an improved role of abnormal glucose and lipids metabolism as well as reducing weight. Here, we describe the protocol of an ongoing clinical trial investigating a new therapy for metabolic syndrome in patients with abnormal glucose metabolism. Methods: This study will enroll 880 subjects (aged 18–70 years) who have Metabolic syndromes with abnormal glucose metabolism. All the participants in a double-blind, parallel, randomized, placebo-controlled trial, will receive Jinlida or placebo, orally, 9g/time, three times daily for 2 to 4 years period on the basis of lifestyle intervention. The primary outcome measure (Incidence of type 2 diabetes) will be assessed during intervention cycles. Adverse events were monitored. All statistical tests will be performed using a two-sided test, and a p-value less than or equal to 0.05 (two-sided test) will be considered to be statistically significant results. Discussion: Results from this study will provide evidence on whether incorporating oral Jinlida granules treatment into lifestyle intervention can delay or inhibit the development of diabetes mellitus in metabolic syndrome subjects with abnormal glucose metabolism. Ethics and dissemination: Ethics approval has been obtained from the Ethics Committees of the Guang anmen hosiptial of China Academy of Chinese Medical Sciences. Dissemination will include submission to peer-reviewed scientific journals and presentation at congresses. Clinical trial registration: Registered at http://www.chictr.org.cn/enIndex.aspx. Trial registration number. ChiCTR1900023241 Keywords: Jinlida Granules; Metabolic Syndrome; Abnormal Glucose Metabolism; Clinical trial